2013
DOI: 10.1007/s00345-013-1024-4
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for the presence of pelvic lymph node metastasis in penile squamous cell carcinoma patients with inguinal lymph node dissection

Abstract: Primary tumor expression of p53, lymphatic or vascular invasion, number of metastatic inguinal lymph nodes and lymph node density were all predictors of pathologic pelvic lymph node involvement. Patients with pelvic LNM had an adverse prognosis, with a 3-year overall survival rate of approximately 12.1%. Pelvic lymph node dissection should be considered in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Nodal burden, represented as number of positive LN, has been shown to be associated with poorer prognosis [71112]. Pandey et al [2] identified a 75.6%, 8.4%, and 0% 5-year survival with patients who had 1–3, 4–5, and >5 nodes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodal burden, represented as number of positive LN, has been shown to be associated with poorer prognosis [71112]. Pandey et al [2] identified a 75.6%, 8.4%, and 0% 5-year survival with patients who had 1–3, 4–5, and >5 nodes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considerable interest has focused on the inguinal lymph node dissection (ILND) which provides valuable pathologic staging [567], guides adjuvant therapy [8], and offers therapeutic benefit [9]. Multiple studies, as reflected in current TNM staging for penile cancer [10], have shown that number of positive lymph node (LN) predicts recurrence-free survival (RFS) and overall survival (OS) [71112]. However, these studies do not account for the extent of ILND, masking the true extent of lymph node involvement.…”
Section: Introductionmentioning
confidence: 99%
“…All patients had squamous cell carcinoma of the penis with unilateral inguinal LNM and pathological confirmation of pelvic nodes following PLND. The decision to perform PLND has changed over time in each contributing center, however, currently is based on the presence of two or more inguinal LNM, the presence of extranodal extension (ENE) or suspicious pelvic imaging [5,6,10]. The extent of the PLND was not standardized between the centers; however, it included external iliac, obturator and internal iliac nodes.…”
Section: Study Populationmentioning
confidence: 99%
“…58 The boundaries of PLND include the iliac bifurcation proximally, ilioinguinal nerve laterally, and the obturator nerve medially. PLND involves removal of the obturator, internal iliac, and external iliac LNs as well as any clinically positive LNs in the pelvis.…”
Section: Surgical Treatment Of Pelvic Lnsmentioning
confidence: 99%